Eco-efficient cold chain networks design. Issue 5 (3rd September 2019) - Zanoni, Simone; Mazzoldi, Laura; Ferretti, Ivan
ABSTRACT: The demand of food distribution across global supply chains is continuously growing and since this kind of deliveries need refrigeration, the growth will enormously increase the energy request and the associated carbon emissions. The aim of this study is to develop a model for the optimisation of eco-efficiency related to a typical refrigerated food distribution network design as a particular case of cold chain. Inventory holding, transportation and energy consumption cost components are included in the model for the evaluation of economic performance of the chain, while energy consumption for storage and transport activities is also considered to contribute to the environmental performance of the chain. In order to model a supply chain related to refrigerated food, the perishability of distributed products is also involved in the model, as it influences storage and distribution activities performances. A novel analytical model is developed for the economic and environmental evaluation of the considered chain. A numerical study that considers different alternative configurations of the distribution network for refrigerated green peas is presented and results are discussed considering the eco-efficiency of different alternatives. Finally, main limitations of the model and future developments are presented and discussed.